1985
DOI: 10.3758/bf03200021
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement expectancy and trial spacing effects in delayed matching-to-sample by pigeons

Abstract: Four experiments assessed the role of reinforcement expectancies in the trial spacing effect obtained in delayed matching-to-sample by pigeons. In Experiment 1, a differential outcome (DO) group received reinforcement with a probability of 1.0 for correct comparison responses following one sample stimulus and a probability of 0.2 for correct comparison responses following the other sample stimulus. The nondifferential outcome (NDO) group received reinforcement with a probability of 0.6 for correct responses to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
2

Year Published

1989
1989
2008
2008

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 24 publications
(46 reference statements)
3
40
2
Order By: Relevance
“…In addition, these data reveal that accuracy declined similarly on high-and low-probabilityof-reinforcement trials as the delay interval was lengthened. Santi and Roberts (1985b) reported a similar result. It appears that the use of differential reinforcement probabilities does not result in a strong bias to select the comparison associated with either the high or the low reinforcement probability as the relevant trial information is lost.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…In addition, these data reveal that accuracy declined similarly on high-and low-probabilityof-reinforcement trials as the delay interval was lengthened. Santi and Roberts (1985b) reported a similar result. It appears that the use of differential reinforcement probabilities does not result in a strong bias to select the comparison associated with either the high or the low reinforcement probability as the relevant trial information is lost.…”
Section: Discussionsupporting
confidence: 76%
“…This study helps to extend the range of conditions under which DO effects can be observed (DeLong & Wasserman, 1981;Santi & Roberts, 1985a, 1985b. The failure of Santi and Savich (1985) to obtain this effect cannot be attributed to their use of a directed forgetting procedure; they probably did not provide sufficient training with 00 conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In every study, including all three that are cited by Wixted and Squire (Trapold 1970;Santi and Roberts 1985;DeMarse and Urcuioli 1993), the differential outcomes (rewards) occur following a correct response to a stimulus or stimulus pairing, and learning of a set of stimulus-response-reward combinations is measured by the increase in performance accuracy (always measured as percent correct) over the course of many repetitions of the same combinations. In other words, this effect involves learning to associate specific stimuli and responses with different rewards, and the effect emerges only after hundreds of repetitions of these specific stimulus-response-reward combinations.…”
Section: The Differential Outcomes Effectmentioning
confidence: 99%